Energy efficient data centers : third International Workshop, E2DC 2014, Cambridge, UK, June 10, 2014, Revised selected papers /: third International Workshop, E2DC 2014, Cambridge, UK, June 10, 2014, Revised selected papers. (2015) - Unknown
No abstract available